Media composition to revive leptospires stored at −80 °C - Philip, Noraini; Neela, Vasantha Kumari (Academic Press, 2022)
Leptospires are preserved by frequent sub-culturing in semisolid media due to the challenge of low recovery by freezing or liquid nitrogen methods. The present study evaluated three liquid EMJH medium compositions (Medium A: Leptospira medium base EMJH, Leptospira enrichment EMJH, 5-fluorouracil (3%), rabbit serum (1%) and calf serum (1%); Medium B: same as Medium A but without 5-fluorouracil; Medium C: same as Medium B but with the addition of sodium pyruvate) for the revival of leptospires after storage at −80 °C. A total of 18 Leptospira serovars cultured in Medium A was aliquoted into cryogenic vials and directly stored at −80 °C. A hundred microlitre from each serovar culture stored at −80 °C was sub-cultured on a selected time over a period of 30 months into Media A, B and C. Regrowth on Media B and C showed a better and faster recovery (89–100%) (p-value <0.05) compared to Medium A (67–100%). Leptospires can be stored longer at −80 °C and a good recovery could be obtained when sub-cultured on EMJH medium without 5-fluorouracil.